DEVELOPMENT OF STUDENT WORKSHEET BASED ON DISCOVERI LEARNING ON TRIGONOMETRIC MATERIALS FOR SENIOR HIGH SCHOOL AT LUBUKLINGGAU CITY - Drajat Friansah; As Elly S; Novianti Mandasar (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
This study aims to (1) Produce Discovery Learning Mathematics Student Worksheets in Trigonometry Material for high school students who are valid and practical; (2) Knowing students' responses to Discovery Learning Mathematics Student Worksheets in Trigonometry Material for Lubuklinggau City High School Students. This type of research is development research with the development of the Tessmer model. The results of the study indicate that: (1) The quality of the LKS produced is valid and practical. Valid is drawn from the results of the analysis after being validated by experts based on content, constructs, and languages with an average score of 4.2 with very valid categories. The practicality of worksheets addresses practical criteria with an average score of 3.6 obtained from the analysis of student practicality questionnaire sheets and 4.6 in very practical criteria obtained from the teacher's response questionnaire analysis. (2) Based on the analysis of the results of student responses to the developed worksheet, a positive response was obtained.